Notes on the (strict and vicarious) liability of the legal entity for crimes committed by individuals integrated in its structure. The Peruvian case. (2022)
The predominant legal opinion in Peru states that the «Administrative Liability of Legal Entities Act» (Act 30424), beyond the employed denomination, stablishes a genuine system of criminal liability of legal entities. The argument widely repeated by the aforementioned predominant legal opinion is that, since this liability is based on a crime and is declared by a criminal judge within the framework and with the guarantees of a criminal procedure, then it has a criminal nature. This study is aimed to provide an opposite approach to the one described, with the objective of proposing that, ultimately, Act 30424 establishes a strict and vicarious liability that is of a civil nature and has its basis in the unjust enrichment of the legal entity due to a crime committed by the natural person, who has acted in the name of the legal entity or on its behalf and for its direct or indirect benefit.